Perfil de citocinas na resposta imune in situ na Leishmaniose cutânea disseminada - Santos, Laécio Paulo Sousa (2018)
Disseminated cutaneous leishmaniasis (LS) is a rare and emerging form of leishmania infection. It begins with a lesion that ulcerates and occurs hematogenous and lymphatic dissemination of the parasite. It is characterized by the presence of 10 or more pleomorphic skin lesions (papular, nodular, acneiform, crusty and ulcerated), affecting two or more anatomical segments of the body and with mucosal involvement. In the New World it is commonly caused by Leishmania (Viannia) braziliensis, with cases with Leishmania (Leishmania) amazonenses, Leishmania guianensis, Leishmania panamensis and Leishmania peruviana, and in the Old World Leishmania tropica and Leishmania major. Its pathogenesis has not yet been clarified, data from the literature suggest that it is due to an immunosuppression. The aim of this study was to evaluate the expression of proinflammatory and antiinflammatory cytokines in the cutaneous lesion of individuals with LCD. A case-control study was conducted, consisting of 8 patients with LCD and 12 patients with LCL. Biopsies of the ulcerated lesions were performed and these samples were submitted to immunohistochemistry to determine the expression of INF-γ, IL-10 and TGF-β. Quantification of cytokine expressing cells in the dermis was determined by counting the labeled and unlabelled cells in 10 400X fields using the Image J program and calculating the relative frequency. In the lesion, there was no significant difference in IFN-γ production by the inflammatory infiltrate cells between the two groups, with a median of 2.0% (LCL) and 4.6% (LCD). As for the anti-inflammatory cytokine, it was verified that in the lesions of the patients with LCD, there was a higher production of IL-10 than in those of LCL, a median of 1.6% and 0.4%, respectively (p = 0.04). Conclusion: The production of IL-10 in cutaneous lesions of patients with LCD was higher than in patients with LCL (p = 0.04), indicating that immunosuppression could be mediated by IL-10.